The Development of Physical Education Learning Models for Mini-Volleyball to Habituate Character Values among Elementary School Students - Sujarwo Sujarwo; Suharjana Suharjana; Hari A. Rachman; Muchamad Arif Al Ardha (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2021)
This research aims to produce, implement, and test the effectiveness of a mini-volleyball learning model, in particular, to habituate character values among elementary schools students. It was conducted using a research development (R&D) method. The research samples comprised 30 physical education teachers and 252 elementary school students. The data were collected using quantitative and qualitative approaches. The research instruments were interview, questionnaires, rubrics, and authentic assessment. The learning model's content validity was tested by seven experts, and construct validity was tested using Explanatory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). Furthermore, the model's effectiveness instrument was developed based on a rubric and authentic assessment to assess character development. The validity was tested by three experts, and the reliability was tested with an interclass correlation (ICC) test. Four inter-rater or independent observers were involved in assessing the model's effectiveness. The results of this study determined that the model of mini-volleyball learning materials successfully habituated the character values of discipline, cooperation, and hard work with a t-value of -11.700 and significant value is 0.000.